2020
DOI: 10.1111/adb.12889
|View full text |Cite
|
Sign up to set email alerts
|

Microglia depletion and alcohol: Transcriptome and behavioral profiles

Abstract: Alcohol abuse induces changes in microglia morphology and immune function, but whether microglia initiate or simply amplify the harmful effects of alcohol exposure is still a matter of debate. Here, we determine microglia function in acute and voluntary drinking behaviors using a colony‐stimulating factor 1 receptor inhibitor (PLX5622). We show that microglia depletion does not alter the sedative or hypnotic effects of acute intoxication. Microglia depletion also does not change the escalation or maintenance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…However, in a recent study, media transfer from ethanol-treated organotypic hippocampal slice cultures (OHSCs) containing microglial microvesicles to naïve OHSCs induced TNFA and other proinflammatory cytokines that was blunted in microglialdepleted ethanol-treated media consistent with microglial vesicular signaling contributing to some aspects of alcohol-induced neuroimmune activation (Crews et al, 2021). Further, while microglia depletion prevents escalations voluntary alcohol intake and concomitant anxiety-like behavior in alcohol dependent mice, it does not affect voluntary ethanol intake in nondependent mice supporting a role for microglia in alcohol dependence (Warden et al, 2021;Warden et al, 2020). The observation that numerous proinflammatory neuroimmune genes are unaltered following microglial depletion in vivo suggests that astrocytes and neurons express higher levels of neuroimmune mediators than previously known.…”
Section: Discussionmentioning
confidence: 95%
“…However, in a recent study, media transfer from ethanol-treated organotypic hippocampal slice cultures (OHSCs) containing microglial microvesicles to naïve OHSCs induced TNFA and other proinflammatory cytokines that was blunted in microglialdepleted ethanol-treated media consistent with microglial vesicular signaling contributing to some aspects of alcohol-induced neuroimmune activation (Crews et al, 2021). Further, while microglia depletion prevents escalations voluntary alcohol intake and concomitant anxiety-like behavior in alcohol dependent mice, it does not affect voluntary ethanol intake in nondependent mice supporting a role for microglia in alcohol dependence (Warden et al, 2021;Warden et al, 2020). The observation that numerous proinflammatory neuroimmune genes are unaltered following microglial depletion in vivo suggests that astrocytes and neurons express higher levels of neuroimmune mediators than previously known.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, the increased microglia in the present study were observed in the absence of reactive astrogliosis, upholding the idea that microglial activation in the binge‐exposed brain is neuroprotective (Melbourne et al, 2019). The progressive increase with ongoing binge exposure is especially interesting in light of recent evidence that microglia may be causal in the escalation of drinking behavior (Warden et al, 2020), potentially contributing to the link between binge drinking and future AUD (Gowin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In both adolescent and adult animal models of AUDs, microglia are activated by excessive ethanol consumption (McClain et al, 2011 ; Crews et al, 2013 ; Marshall et al, 2013 ; Peng et al, 2017 ; for review see Crews et al, 2016 ; Melbourne et al, 2019 ) and manipulating neuroimmune signaling drives alcohol consumption in some models (Agrawal et al, 2011 ; Blednov et al, 2011 ). The specific role of microglia, however, has been less clear (Walter and Crews, 2017 ; Warden et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%